Preliminary Aerodynamic and Aerothermodynamic Assessment of the VTO Hopper Booster. (4th May 2011) - Pezzella, Giuseppe
Abstract : Within the framework of the Future Launchers Preparatory Program, carried out by the European Space Agency, the VTO-Hopper reusable launcher is investigated. This concept is a winged sub orbital vehicle designed for vertical take-off with an expendable upper stage, able to deliver a payload up to 8 Mg in geostationary transfer orbit. After the staging, the reusable booster will re-enter the Earth's atmosphere, and then perform a downrange landing. In this paper the current design activities are described. The goal has been to define the preliminary booster aerodynamic and aerothermodynamic databases. Therefore, the aerothermal environment that the vehicle will encounter along its lifting reentry has been provided and analyzed. Different design approaches have been addressed. In fact, aerodynamic and aerothermodynamic analyses have been performed by using both engineering and numerical methods. For instance, a 3D Panel Methods code, typical for hypersonics, has been employed; the heat flux distributions have been evaluated by means of improved boundary layer methods. Increasing the order of complexity, a number of detailed 3D CFD analyses have been performed for different flight conditions along the descent trajectory. Results show that the aerodynamics and aerothermodynamics derived from engineering design approach are valid only for preliminary analysis purposes.